Combinational Use of Antiplatelet Medication Sarpogrelate with Therapeutic Drug Rosuvastatin in Treating High-Cholesterol Diet-Induced Chronic Kidney Disease in ApoE-Deficient Mice. (27th September 2020) - Xu, Jingyi; Pei, Zuowei; Yu, Meng; Li, Xiang; Wang, Lu; Lin, Yichen; Chen, Xinyan; Liu, Xiaodan
Abstract : A number of metabolic disorders, including hyperlipidemia, potentially cause chronic kidney disease (CKD), one of their major chronic complications and comorbidities. Rosuvastatin is one of the widely used antiatherogenic drugs among hyperlipidemic patients. Meanwhile, sarpogrelate is not only a 5-hydroxytryptamine receptor antagonist but also an antiplatelet agent, inhibiting platelet-stimulated blood coagulation and improving peripheral circulation. In this study, a combination of sarpogrelate and/or rosuvastatin was used on CKD mice induced by a high-fat diet for 8 weeks. The mice were tested for pathological changes using histological evaluation. Tremendous alterations were found, including a remarked increase in total cholesterol and low-density lipoprotein cholesterol levels, glomerular endothelial proliferation, and mesangial expansion. Also, tubular damage and extracellular matrix accumulation occurred, namely, a marked increase in the macula densa, scattered and apoptotic loss of the apical brush border with vacuolated basophilic cytoplasm and heavily stained nuclei, and expanded Bowman's space, which were at least partially ameliorated by sarpogrelate and/or rosuvastatin treatment. The analysis of expression profiles at both the RNA and protein levels, using real-time quantitative polymerase chain reaction and Western blot analysis, indicated that LDL-R/CD68/LOX-1-positive monocyte/macrophage-mediated enhanced proinflammatory activation, including the significant upregulation of tumor necrosis factor- α and interleukin-6, was actually attenuated by sarpogrelate and/or rosuvastatin treatment. The findings indicated that sarpogrelate and/or rosuvastatin treatment potentially ameliorates CKD progression in patients with the aforementioned comorbid metabolic disorders.